2006
DOI: 10.1134/s1087659606040122
|View full text |Cite
|
Sign up to set email alerts
|

Monotectic crystallization of melts in the ZrO2-Al2O3 system

Abstract: The morphology of the crystalline phases prepared at different cooling rates, temperatures, and compositions of melts in the ZrO 2 -Al 2 O 3 system is investigated. It is established that both the quenched and slowly crystallized samples containing 35-70 wt % ZrO 2 have a submicron structure. Outside this concentration range, the ingots have a zonal structure: the peripheral region is formed by large baddeleyite crystals (at a ZrO 2 content higher than 70 wt %) or corundum crystals (at a ZrO 2 content lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…An analysis of the quenched rod samples in our earlier work [2] and in this study demonstrates that the crystallization in the ZrO 2 -Al 2 O 3 system is characterized by specific features due to the presence of the liquid-liquid phase separation region. It should be noted that these features differ from those observed in crystallization of melts in systems with a complete miscibility in the liquid state.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…An analysis of the quenched rod samples in our earlier work [2] and in this study demonstrates that the crystallization in the ZrO 2 -Al 2 O 3 system is characterized by specific features due to the presence of the liquid-liquid phase separation region. It should be noted that these features differ from those observed in crystallization of melts in systems with a complete miscibility in the liquid state.…”
Section: Resultssupporting
confidence: 59%
“…However, the data on the phase diagram of this system are contradictory (see discussion in [1,2]). In [1,2], it was experimentally revealed that the liquid-liquid phase separation region exists in the ZrO 2 -Al 2 O 3 system. In the present study, we investigated the crystallization of melts in the ZrO 2 -Al 2 O 3 system with the aim of elucidating the mechanism of liquid-liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…In the glass-ceramic system keatite mixed crystal ZrTiO 4 is formed in the presence of TiO 2 and ZrO 2 [50]. Thus an influence by the nucleation of ZrO 2 or various Zirkoniumtitanates respectively in this ternary system is very likely to appear [34,51,52]. The effect of spinodal demixing might provide embryonic crystals inducing nucleation during the rapid cooling.…”
Section: Discussionmentioning
confidence: 99%
“…The existing classifications of eutectic structures are mostly based on dependence of the morphological and dimensional features of the co-crystallizing phases on the cooling conditions of the melt during its crystallization [12]. It was established [13,14] that the preparation of the finely dispersed eutectics (fine-grained phase mixtures) is possible at cooling rates ~ 10 6 °/С and higher.…”
Section: Literary Sources Reviewmentioning
confidence: 99%